"Change-makers in midwifery care": Exploring the differences between expectations and outcomes—A qualitative study of a midwifery net-based education programme in the Somali region. (February 2019) - Hatakka, Mathias; Osman, Fatumo; Erlandsson, Kerstin; Byrskog, Ulrika; Egal, Jama; Klingberg-Allvin, Marie
Abstract: Objective: The aim of this study is to explore midwifery educators' expected outcomes in the net-based master's programme, the programmes' realised outcomes and the reported difference regarding the increased choices for the graduates and the effect on their agency. Design: In this case study, we focused on a net-based master's programme in sexual and reproductive health in Somalia. Somalia suffers from a shortage of skilled birth attendants and there is a need for building up the capacity of midwifery educators. Setting and participants: Data was collected in focus group discussions at the start of the programme and eight months after the students graduated. The data were analysed through the lens of the choice framework, which is based on the capability approach. Findings: Findings show that many of the graduates' expectations were met, while some were more difficult to fulfil. While the midwives' choices and resource portfolios had improved because of their role as educators, the social structure prevented them from acting on their agency, specifically in regards to making changes at the social level. Several of the positive developments can be attributed to the pedagogy and structure of the programme. Conclusion: The flexibility of net-based education gave the midwifery educators a new educational opportunity that they previously did not have. Students gained increased power and influence on some levels. However, they still lack power in government organisations where, in addition to their role as educators, they could use their skills and knowledge to change policies at the social level.